2019
DOI: 10.1111/josh.12847
|View full text |Cite
|
Sign up to set email alerts
|

Health Empowers You: Impact of a School‐Based Physical Activity Program in Elementary School Students, Georgia, 2015‐2016

Abstract: BACKGROUND: Most youth in the United States do not meet the recommended 60 minutes of daily physical activity (PA). The school environment offers an opportunity to engage students in PA. The purpose of this study was to evaluate the impact of a comprehensive school-based physical activity program on student PA across student-level and school-level characteristics. METHODS:PA levels from 3294 fourth grade students in 24 intervention schools and 7 control schools in metropolitan Atlanta, Georgia were measured du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…To avoid risking negative effects of ECPAs on health issues such as stress—which other studies also have identified [ 33 , 34 ]– it is of uttermost importance that schools provide basic structural conditions for ECPAs. Like other studies [ 3 , 4 , 5 , 6 , 25 , 28 , 29 , 31 ], our results also suggest that it is imperative that both students and teachers be involved in the activities, that school personnel are educated and that motivation and lust are all necessary conditions for ECPAs. Hence, the importance of including the students’ perspectives in the planning and implementation of ECPAs with the objective of improved health.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…To avoid risking negative effects of ECPAs on health issues such as stress—which other studies also have identified [ 33 , 34 ]– it is of uttermost importance that schools provide basic structural conditions for ECPAs. Like other studies [ 3 , 4 , 5 , 6 , 25 , 28 , 29 , 31 ], our results also suggest that it is imperative that both students and teachers be involved in the activities, that school personnel are educated and that motivation and lust are all necessary conditions for ECPAs. Hence, the importance of including the students’ perspectives in the planning and implementation of ECPAs with the objective of improved health.…”
Section: Discussionsupporting
confidence: 85%
“…Since habits are established during childhood, interventions such as increased physical activity and information about physical activity to children and their parents seem to be successful factors for achieving these habits [ 1 , 2 , 3 , 4 , 5 , 6 ]. Physical activities in school have been studied and shown to be important factors when it comes to wellbeing and health [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior evaluations of Health Empowers You! document improvements in average daily steps, moderate-to-vigorous PA (MVPA) levels in physical education (PE) classes, and student tness and BMI 16,17 . The intervention was implemented with the goal of sustainably elevating student school-day MVPA.…”
Section: A Study Designmentioning
confidence: 99%
“…Other studies reported a dose‐response relationship between physical activity and health, indicating that the more physical activity, the greater the health benefit 23 . For school‐aged children, evidence suggests that moderate‐to‐vigorous or vigorous physical activity during physical education (PE) classes increased after PE‐based physical activity interventions 24‐28 . However, several studies report that cardiopulmonary fitness does not improve after interventions despite increases in physical activity levels 29‐32 .…”
mentioning
confidence: 99%